Understanding online safety behaviors: A protection motivation theory perspective. Issue 59 (June 2016) - Tsai, Hsin-yi Sandy; Jiang, Mengtian; Alhabash, Saleem; LaRose, Robert; Rifon, Nora J.; Cotten, Shelia R.
Abstract: Internet users experience a variety of online security threats that require them to enact safety precautions. Protection motivation theory (PMT) provides a theoretical framework for understanding Internet users' security protection that has informed past research. Ongoing research on online safety recommends new motivational factors that are integrated here in a PMT framework for the first time. Using PMT, a cross-sectional survey ( N  = 988) of Amazon Mechanical Turk (MTurk) users was conducted to examine how classical and new PMT factors predicted security intentions. Coping appraisal variables were the strongest predictors of online safety intentions, especially habit strength, response efficacy, and personal responsibility. Threat severity was also a significant predictor. Incorporating additional factors (i.e., prior experiences, subjective norms, habit strength, perceived security support, and personal responsibility) into the conventional PMT model increased the model's explanatory power by 15%. Findings are discussed in relation to advancing PMT within the context of online security for home computer users.